Stability Analysis and Robust H∞ Control of Switched Stochastic Systems with Time-Varying Delay - Zhengrong Xiang; Guoxin Chen (Journal of Applied Mathematics)
The problems of mean-square exponential stability and robust H∞ control of switched stochastic systems with time-varying delay are investigated in this paper. Based on the average dwell time method and Gronwall-Bellman inequality, a new mean-square exponential stability criterion of such system is derived in terms of linear matrix inequalities (LMIs). Then, H∞ performance is studied and robust H∞ controller is designed. Finally, a numerical example is given to illustrate the effectiveness of the proposed approach.